THE TATTOO AS ANCESTRAL LEGACY AND DICHOTOMIC ELEMENT OF NATIONAL IDENTITY - Mónica Santillán Trujillo; Víctor Villavicencio Alvarez; Lorena Caiza Morales; Eunice Ayala; Teresa Sánchez Manosalvas (Bina Nusantara University, 2018)
Nowadays, tattoos are associated mostly with fashion; nevertheless, tattooing can constitute a tool of national identity due to its ancestral relation with the Latin American native culture.With regard to the art of the state, no work can be found that analyzes this specific topic. This paper discusses the determinant footprint of ancient symbols in the culture and its actual use as a national identity element. The study uses a deductive method and qualitative analysis to clear the situated premises and ascertain the problem solution through the use of ancient icons in tattoos as identity symbols, which may be reconstructed from the consideration that supports the national proud and development. Although the results still present a low percentage of users, there are citizens who don tattoos. The concept about its representation is positive, and the use of tattoo as an element of identity was found among 50% of citizens. This leads us to conclude that it is, indeed, used in this sense and that the trend could progressively increase. In order to validate this premise, a quarter of the population was necessary.